2018
DOI: 10.14444/5038
|View full text |Cite
|
Sign up to set email alerts
|

Combined Aorto-Iliac and Anterior Lumbar Spine Reconstruction: A Case Series

Abstract: Background: Treatment options for aortic-iliac pathology may include endovascular repair and open surgical repair. Treatment options for degenerative disc disease (DDD) are varied but commonly include anterior reconstruction. When both the aortic-iliac and spinal pathologies are significant and surgical intervention is indicated for each pathology, the opportunity exists for concurrent treatment of both the aortic-iliac pathology and DDD in the same operation. The purpose of this case series was to document th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…[2] As far as the occlusive atherosclerotic process is chronic, it leads to development of collateral blood vessels supplying the affected extremities, hence the clinical tissue ischemia and the cutaneous injury features may occur in different interval and severity. [3,4] It has been reported that the coexistence of AIOD, abdominal aortic aneurysm, ischemic heart disease, and cerebrovascular disease carry a very poor prognosis. [5] Based on the morphology and the level of lesions, the Trans-Atlantic Inter-Society Consensus (TASC) guidelines classified aortoiliac atherosclerotic disease TASC II C and D types and the standard recommended treatment is bilateral surgical bypass of the femoral arteries.…”
Section: Introductionmentioning
confidence: 99%
“…[2] As far as the occlusive atherosclerotic process is chronic, it leads to development of collateral blood vessels supplying the affected extremities, hence the clinical tissue ischemia and the cutaneous injury features may occur in different interval and severity. [3,4] It has been reported that the coexistence of AIOD, abdominal aortic aneurysm, ischemic heart disease, and cerebrovascular disease carry a very poor prognosis. [5] Based on the morphology and the level of lesions, the Trans-Atlantic Inter-Society Consensus (TASC) guidelines classified aortoiliac atherosclerotic disease TASC II C and D types and the standard recommended treatment is bilateral surgical bypass of the femoral arteries.…”
Section: Introductionmentioning
confidence: 99%